RANCANGAN SISTEM INFORMASI AKUNTANSI TERKOMPUTERISASI SIKLUS PENGGAJIAN UNTUK MENINGKATKAN PENGENDALIAN INTERNAL PADA PERUSAHAAN DISTRIBUTOR MINUMAN RINGAN BERKARBONASI DI SURABAYA - ROSALINA, IRENE (: 2303-1719)
PT X is a carbonated soft drinks distributor company in Surabaya. Up till now, this firm is using a manual system for payroll cycle, which is no longer adequate because it cannot fulfil the need of payroll information. The information obtained was often inaccurate and to get it, it needed a lot of time and human resource. Therefore, a computerized accounting information system which could fulfil the need of the firm about some accurate and prompt information that could minimize the mistakes occurred in the firm was designed. This research was a descriptive research through a case study. The qualitative data used was from the internal resource, in the form primary data obtained from the research source. The methods used were introduction study, field study including observations, interviews and documentations. The results of this study produces output design, input design, database design, control of input and output, analysis and discussion of the conceptual design of a Data Flow Diagram and ERD data modeling and physical design of the design of output, input, database, control the output and input. It is expected that the cycle of accounting information systems are computerized payroll and wage, salary data and information on wages can be obtained in a timely and accurate, and can minimize the errors that occur so as to improve internal control.